Transforming East Asia : The Evolution of Regional Economic Integration - Munakata, Naoko, 1962- (Book collections on Project MUSE., 2006)
"Analyzes developments in the region since the mid-1980s, highlighting such factors as the evolution of Asia-Pacific Economic Cooperation, the impact of the 1997-98 Asian financial crisis, and the rise of China. Outlines possible future scenarios for the region and offers policy prescriptions for building on regionalism's achievements to date"--Provided by publisher